Parental gender preferences in Central and Eastern Europe and differential early life disadvantages - Michał Myck; Monika Oczkowska; Izabela Wowczko (Economics of Transition and Institutional Change, 2023)
Parental gender preferences may affect partnership decisions and as a result lead to early life disadvantages. We study these preferences in five post-communist countries of Central and Eastern Europe, a region with strong traditional gender norms and persisting inequalities between women and men in labour market outcomes. Using subsamples of census from Belarus, Hungary, Poland, Romania and Russia around 2000 and 2010, we follow Dahl and Moretti (2008), The demand for sons, to examine the effect of the gender of the first-born child(ren) on fertility decisions and relationship stability of their parents. We only find strong evidence of `boy preferences' in fertility decisions in the cases of Romania and Russia. However, unlike Dahl and Moretti (2008), The demand for sons, for the US, we cannot confirm a relationship between the children's gender and parental partnership decisions. This is the case for all examined Central and Eastern European countries, as well as for a number of countries from Western Europe. The cases of Romania and Russia raise questions about other potential consequences of the documented gender preferences. We argue that our approach can be applied more broadly to identify other countries characterised by parental gender preferences, and to motivate further examination of different forms of gender driven early life disadvantages.
Keywords: 330; early life discrimination; family structure; fertility decisions; parental gender preferences; transition countries